Embedding of Circulant Networks into Wheels. Issue 1 (January 2021) - Mary, Stalin; Rajasingh, Indra
Abstract: Circulant graphs have been studied over many years because of its vast applications in telecommunication industry. We find the minimum wirelengths of embedding the circulant graph G ( n ; ±1, 2) and G ( n ; ±1, 2, …, j ) into variation of wheel graphs on n vertices in this paper.